Effect of regenerated cellulose of ultrafiltration membranes on POME treatment - Azmi, Nazatul Shima; Md. Yunos, Khairul Faezah (Penerbit Universiti Teknologi Malaysia, 2014)
Palm oil mill effluent (POME) in palm oil industry has become a big issue of environmental pollution to be solved urgently and critically. This wastewater consists of water, oil, and natural sediments. Hence, in this study, the work was carried out to investigate ultrafiltration process feasibility for treating palm oil mill effluent. Palm kernel shell bioactivated carbon (PKS-AC) adsorbent was used in adsorption treatment (pre-treatment) was used to reduced solid particles in POME. For adsorption treatment, POME was stirred with 0.20 g/L of PKS-AC at 39.94 minute and sediment for one hour. Membrane separation was subsequently applied to further treat the pre-treated POME. In this study, the permeate flux was found to be dependent to pressure applied, solution pH and stirring speed. An optium conditions was achieved at pressure 2 bar, with solution pH 8 using stirring speed 600 rpm. Considerable amount of POME pollutant is also reduced by used membrane for TS, DS, SS, BOD5, COD and turbidity were 625.32 mg/L, 445.32 mg/L, 180 mg/L, 1296 mg/L, 541.76 mg/L, and 16.20 NTU respectively. Thus, this result show that the pollutant in POME was reduced significantly using this technique.